1991
DOI: 10.1055/s-2006-960312
|View full text |Cite
|
Sign up to set email alerts
|

Topical Anti-Inflamatory Activity of Some Iridoids and Phenylpropanoids

Abstract: Six iridoids and one phenylpropanoid isolated from Loniceru implexu Aiton (Caprifoliaceae), Phlomis cr/n/ta Cay. (Lamiaceae), and Scrophularia auriculuta L. (Scrophulariaceae) were tested for topical anti-inflammatory activity. Since no reports on their pharmacological activity have been published, the present work was undertaken to determine whether they have any topical anti-inflammatory effect. L. implexa and P. cnn/f a were collected in Corhera, Valencia (Spain) and S. auniculata in Sueca, Valencia (Spain). Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…1). Some species of the genus Scrophularia are traditionally used in folk medicine, for example S. ningpoensis in Chinese medicine for treatment of inflammation (1), and some iridoids isolated from S. auriculata have shown anti-inflammatory activity (2).…”
Section: Introductionmentioning
confidence: 99%
“…1). Some species of the genus Scrophularia are traditionally used in folk medicine, for example S. ningpoensis in Chinese medicine for treatment of inflammation (1), and some iridoids isolated from S. auriculata have shown anti-inflammatory activity (2).…”
Section: Introductionmentioning
confidence: 99%
“…Scrophularia auriculata, with the highest activity in the study of DTH, can be considered the most active species in the different models. In a previous study (Giner et al, 1991) we demonstrated the activity of this species on the acute TPA test, and isolated different iridoids as active principles.…”
Section: Discussionmentioning
confidence: 80%
“…Two catalpol derivates 12)], isolated from S. auriculata L., exert high antiinflammatory activity on mouse ear edema induced by tetradecanoylphorbol acetate (TPA). When these products were assayed at the same dose as indomethacin (0.5 mg/ear), they exhibited nearly the same effect as this reference drug with an edema percentage inhibition of 73.4% (Giner et al, 1991).…”
Section: Antiinflammationmentioning
confidence: 89%